A computational study on the mixing and reduction of slags from ferrochrome and stainless steel production. (December 2021) - Heikkinen, Eetu-Pekka; Heikkilä, Anne; Vallo, Kimmo; Ikäheimonen, Topi; Fabritius, Timo
Abstract: Large amounts of slags are formed in the production of ferrochrome and stainless steels. Although there are many suitable applications for ferrochrome slag products, some chromium is lost with the slag. On the other hand, utilisation of some stainless steel slags are hindered by the volumetric changes of the dicalcium silicate, which is formed during the solidification and cooling of slags. Furthermore, there is some chromium also in stainless steel slags and its recovery would significantly improve the material efficiency and decrease the environmental impact of the stainless steel production. The purpose of this study was to estimate the possibilities to overcome these hindrances by mixing different slags with different ratios thus creating slags in which no dicalcium silicate is formed during solidification and from which chromium could be reduced in one process step before solidification of the slag. Carbon, methane and ferrosilicion were considered as possible reductants in this study. The study was conducted in three stages in which thermochemical simulations were used to estimate the solidus and liquidus temperatures of different slag mixtures, amounts of reductants required to reduce chromium from the slag mixtures and finally the needs for additional energy in the reduction process. The results of thermodynamic simulations were used to define suitable slag mixing ratios for chromium recovery taking avoidance of dicalcium silicate formation, distribution of chromium between different phases as well as the amounts of different possible reactants required for chromium recovery into account. According to the results, at least 30% of ferrochrome production slags are required in the mixtures in order to avoid the formation of dicalcium silicate, whereas the excessive use of ferrochrome slags increases the amount of solid spinel phase in the system thus making the chromium recovery more challenging.